THE RELEVANCE OF THE MANAGEMENT SYSTEM AND THE INTEGRATION OF EDUCATION - Maxkamov Navruzjon Tukhtamishevich (FAN, TA’LIM VA AMALIYOT INTEGRATSIYASI, 2021)
This article highlights the importance and relevance of the combination of management system and education, offers opportunities and mechanisms for combining the management system and education in public administration of the Republic of Uzbekistan.